Landscape–Geochemical Assessment of Content of Potentially Toxic Trace Elements in Arctic Soils - Evgeny Lodygin; Ivan Alekseev; Boris Nesterov (Soil Systems, 2024)
The importance of research to assess the impact of potentially toxic trace elements (PTEs) on the environment and the importance of environmental monitoring, taking into account the natural variability of soil properties, shaped the aim of our study: to determine the background concentrations of PTEs in different soil profiles in the European Northeast, specifically in the Republic of Komi in Russia, taking into account the landscape and geochemical characteristics of the area. We analysed 173 soil samples from five main soil subtypes. The acid soluble forms of PTEs (Cu, Pb, Zn, Ni, Cd and Mn) were measured using an atomic emission spectrometer. We developed a database of PTE contents and created distribution maps for the Komi Republic using GIS technologies. The study found that PTE levels in soils from accumulative landscapes (such as depressions and floodplains) were generally higher than those in soils from eluvial landscapes (interfluves). We identified correlations between the levels of different PTEs and certain soil properties, providing insights into the biogeochemical migration patterns of these elements. The differentiation of PTEs in soil profiles was more pronounced in loamy automorphic soils and less so in sandy semi-hydromorphic and hydromorphic soils. Most soils, except floodplain soils, showed a clear eluvial–illuvial pattern of PTE distribution within the mineral soil profile, whereas floodplain soils showed a more uniform PTE distribution. The results of this study are useful for assessing the contamination levels of these soil types in high-latitude regions.